Evaluation of the kinetics of oxidation and removal of organic matter in the self-purification of a mountain river (2015)
The study is based on the determination of the kinetic rates and assessment of self-purification of the Frio River, due to the uptake of organic load. The kinetic rates were calculated by applying differential and logarithmic methods on concentrations of water quality determinants present in each of the (7) reach of the river. The water system easily recovers the amount of oxygen, kd= 0.4, ka 3.2 d-1, only receives 27.7 Ton. d-1, the organic load, making high concentrations of carbon, ammonium and remain sediment. The length Influence of discharges, LIV- BOD yielded a mean per tranche of 10 km, compared to 3 km each way, means that the river can´t self- purification that need more length of travel. The study illustrates the modeling of the determinants of quality, developed by the QUAL2K, using the calculated rates.